Borders of Authority: Power in the Canadian Borderlands at the 1844 Jesuit-Anishinaabeg Debate. Issue 3 (3rd July 2017) - Jurss, Jacob C.
ABSTRACT: In 1844 a debate took place between a venerated Anishinaabeg orator and an ambitious Jesuit priest over who possessed the authority to harvest timber from Walpole Island. Though scholars have taken notice of this unique debate recorded in the Letters from the New Canada Missions the circumstances and backgrounds of the central orators, Anishinaabeg ogimaa Oshawana and Jesuit priest Father Pierre Chazelle, has not been analyzed. The debate centered on how each society viewed the natural world and the natural resources necessary for survival. The power struggle represented by each man in the Canadian borderlands highlighted the differences between European Jesuit understanding and First Nation Anishinaabeg understanding of their place and relationship to the greater world. How each society understood power and how to wield said power was illuminated in the contested discussion between the two men. Thus the debate, while containing strong themes of religious and spirituality, has much to say about the larger goal of Euro-Canadians to "civilize" First Nation peoples while providing an equally compelling argument made by Oshawana for cultural pluralism and a defense of First Nation sovereignty.